Long-term changes in the distribution and abundance of nine deep-water skates (Arhynchobatidae: Rajiformes: Chondrichthyes) in the Northwestern Pacific - Orlov, Alexei M. 1960- (Animals)
Simple Summary Changes in the spatial distribution and abundance of common skate species of the genus Bathyraja in the Russian waters of the Northwestern Pacific, where their fishery is considered promising, but still not developed, are traced. Over the past six decades, the boundaries of their ranges have slowly fluctuated near some average annual position and abundance trends have coincided with previously identified ecosystem rearrangements under the influence of climatic and oceanological changes. It will be useful to compare the results obtained with abundance trends in the near future, when fishing for these species is expected to intensify here, as well as with other areas where fishing pressure for these species already exists. Based on the analysis of long-term data from bottom trawl surveys (1977-2021), changes in the spatial distribution, position of the boundaries of the ranges and the catch rates of the nine most common deep-sea skates of the genus Bathyraja in the Russian waters of the Northwestern Pacific (B. violacea, B. aleutica, B. matsubarai, B. maculata, B. bergi, B. taranetzi, B. minispinosa, B. interrupta, and B. isotrachys) are considered. During the surveyed period, significant changes in the spatial distribution were observed, which are probably due to both subjective reasons (changes in the number of trawling stations, surveyed depths, etc.) and climatic changes. No monotonous displacement of the northern or southern boundaries of the range or its center in one direction was observed in any area of any species during the entire observation period. At the same time, shifts in the boundaries of the ranges of different species in different areas occurred for different decades, i.e., the boundaries of the ranges slowly fluctuated or pulsed near some average annual position. In general, from the 1970s to the 1980s, the number of skates grew; from the 1980s to the 1990s, it decreased; from the 1990s to the 2000s, it fluctuated at the achieved level; from the 2000s to the 2010s, it grew again; and from the 2010s to the 2020s, it decreased again. These trends coincide with previously identified ecosystem rearrangements under the influence of climatic and oceanological changes. The identification of links between changes in spatial distribution, range boundaries and catch rates with climatic and oceanological factors require separate additional studies.